2023
DOI: 10.7150/ijbs.87975
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Complex Interplay between Epigenetics and Immunity in Alcohol-Associated Liver Disease: A Comprehensive Review

Yali Liu,
Tao Liu,
Feiyu Zhang
et al.

Abstract: The mechanisms of immune dysfunction in alcohol-associated liver disease (ALD) have garnered growing research interest in recent times. Alcohol-mediated immune dysfunction has been implicated as a potential cause of ALD-associated microbial infection and inflammatory response. The immune microenvironment of an organism is essentially a complex network of interactions between immune cells, cytokines, extracellular matrix, and other immune-related molecules. This microenvironment is highly adaptive and responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…For example, it has demonstrated that the liver is a potential target of IL-19, IL-20, and IL-24 in the acute phase response [ 15 ]. Possible therapeutic approaches for the treatment of ALD could be the downregulation of IL-20 and the upregulation of IL-22 ratios through acquired epigenetic mechanisms [ 16 ]. Table 1 lists the roles of IL-20 subfamily members in liver diseases.…”
Section: Overview Of Il-20 Cytokinementioning
confidence: 99%
“…For example, it has demonstrated that the liver is a potential target of IL-19, IL-20, and IL-24 in the acute phase response [ 15 ]. Possible therapeutic approaches for the treatment of ALD could be the downregulation of IL-20 and the upregulation of IL-22 ratios through acquired epigenetic mechanisms [ 16 ]. Table 1 lists the roles of IL-20 subfamily members in liver diseases.…”
Section: Overview Of Il-20 Cytokinementioning
confidence: 99%
“…Alcohol-induced changes in histone modification enzyme expression and activity affect multiple innate and adaptive immunity cell populations [36][37][38][39][40][41][42]. Alcohol-induced epigenetic changes were described for several types of immune cells (e.g., granulocytes, macrophages, and T-lymphocytes) and are thought to promote exaggerated inflammatory responses in ALD.…”
Section: Immune Cell Epigenetic Changesmentioning
confidence: 99%
“…The roles of other histone modification enzymes and DNA methylation in immune cell phenotype were not specifically explored in ALD. However, the data from other disease models suggest that they could be implicated in altered cytokine production in macrophages and dendritic cells as well as altered CD8 + and CD4 + T cell phenotypes that promote liver injury and enhance alcohol-induced liver disease progression [37,40].…”
Section: Immune Cell Epigenetic Changesmentioning
confidence: 99%